2012
DOI: 10.1007/s00330-011-2367-0
|View full text |Cite
|
Sign up to set email alerts
|

CT colonography without cathartic preparation: positive predictive value and patient experience in clinical practice

Abstract: • Computed tomographic colonography (CTC) without cathartic preparation is well accepted by patients • Cathartic-free faecal tagging CTC yields high positive predictive values • CTC without cathartic preparation could improve uptake of colorectal cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
(69 reference statements)
0
15
1
Order By: Relevance
“…Low specificities may partly reflect the high prevalence of abnormality in the gFOBt/FIT positive population, potentially leading radiologists to report equivocal findings as positive (to maximise sensitivity). Furthermore, the minimum level of radiologist experience (50 to 100 cases) was substantially lower than the studies reporting high PPV (minimum 300 cases) [33,34]. Additionally, faecal tagging was not used in the study with the lowest specificity [29], which reported that most of the false-positives were due to faecal residue.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Low specificities may partly reflect the high prevalence of abnormality in the gFOBt/FIT positive population, potentially leading radiologists to report equivocal findings as positive (to maximise sensitivity). Furthermore, the minimum level of radiologist experience (50 to 100 cases) was substantially lower than the studies reporting high PPV (minimum 300 cases) [33,34]. Additionally, faecal tagging was not used in the study with the lowest specificity [29], which reported that most of the false-positives were due to faecal residue.…”
Section: Discussionmentioning
confidence: 63%
“…Specificity and PPV were less good, with the latter ranging from 62 to 88%, somewhat lower than the 92-93% reported when CTC is used for asymptomatic screenees [33,34]. The pooled estimate of specificity was 75.4%, although heterogeneity was high.…”
Section: Discussionmentioning
confidence: 77%
“…What can be assessed are the true-positive versus false-positive studies, allowing for determination of positive predictive value (PPV), which serves as an important quality measure in clinical practice. 7,8 In our experience, the PPV for lesions ≥ 6 mm should be generally be above 90% at CTC in routine clinical practice. 7 The true-positive results from CTC also be used to compare against the expected prevalence of disease (eg, for advanced neoplasia).…”
Section: Clinical Trial Versus Clinical Practice Settingmentioning
confidence: 74%
“…One useful feature at CTC that likely improves detection of flat lesions is the tendency for oral contrast to adhere to their surface. As noted above, the PPV for flat lesions detected at CTC is considerably lower [14,15], which likely reflects a combination of over-calling (i.e., CTC false positives) and lesions missed at optical colonoscopy (i.e., colonoscopic false negatives). Carpet lesions, also referred to as ‘laterally spreading tumors’, are large (≥ 3 cm) flat lesions that are most often found in the cecum and rectum.…”
Section: Other Computed Tomography Colonography Performance Datamentioning
confidence: 99%
“…Recent noteworthy advances in CTC technique include new data on noncathartic bowel preparations [15,21 ▪▪ ,23 ▪▪ ] and computer-aided detection (CAD) [24,25]. Potential benefits of noncathartic or laxative-free CTC include improved patient acceptance and adherence, but these must be weighed against the potential disadvantages, which include the inability for same-day polypectomy and reduced accuracy.…”
Section: Technical Advancesmentioning
confidence: 99%